2019
DOI: 10.1186/s12933-019-0942-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exenatide and open-label SGLT2 inhibitor treatment, given in parallel or sequentially, on mortality and cardiovascular and renal outcomes in type 2 diabetes: insights from the EXSCEL trial

Abstract: BackgroundSodium-glucose cotransporter-2 inhibitors (SGLT2i) and glucagon-like peptide-1 receptor agonists (GLP-1 RA) improve cardiovascular and renal outcomes in patients with type 2 diabetes through distinct mechanisms. However, evidence on clinical outcomes in patients treated with both GLP-1 RA and SGLT2i is lacking. We aim to provide insight into the effects of open-label SGLT2i use in parallel with or shortly after once-weekly GLP-1 RA exenatide (EQW) on cardiorenal outcomes.MethodsIn the EXSCEL cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 43 publications
3
56
0
Order By: Relevance
“…Once a diabetic population develops arrhythmias, they have a worse prognosis [7]. Sodium-glucose cotransporter-2 (SGLT2) inhibitors as antihyperglycemic drugs are proven to have a cardiovascular protective effect in reducing cardiovascular death and hospitalization for heart failure (hHF) in large randomized trials [8][9][10]. Animal studies and clinical trials have shown a sympathoinhibitory effect by SGLT2 inhibitors, which play an important role in arrhythmogenesis [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Once a diabetic population develops arrhythmias, they have a worse prognosis [7]. Sodium-glucose cotransporter-2 (SGLT2) inhibitors as antihyperglycemic drugs are proven to have a cardiovascular protective effect in reducing cardiovascular death and hospitalization for heart failure (hHF) in large randomized trials [8][9][10]. Animal studies and clinical trials have shown a sympathoinhibitory effect by SGLT2 inhibitors, which play an important role in arrhythmogenesis [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the CV protective effect for GLP1RA can be seen in most patients with T2DM; therefore, all patients that have established or at high risk of CVD would benefit from being initiated on GLP1RA regardless of their age, duration of diabetes, and HbA1c level. Moreover, when using one of the GLP1RAs, the addition of another agent with CV protective effect, such as one of the SGLT2i, can contribute to even better CV outcomes in these patients [37]. Therefore, in patients with established or at high risk of CVD when additional therapy is needed for better control of diabetes, agents with CV protective effect should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with T2D and a recent acute coronary event, no difference was observed in the rates of MACE between lixisenatide and placebo [38] and the trial testing once weekly exenatide showed non-significant reductions in 3P-MACE versus placebo [39]. With regards to the latter, it is of interest that the combination with SGLT-2 inhibitors may potentiate the cardiovascular protection exerted by once weekly exenatide [40]. Yet, it has been speculated that cardiovascular protection might be conveyed selectively by human-based GLP-1RA (liraglutide, semaglutide, dulaglutide, albiglutide) and not by exendin-based GLP-1RA (exenatide and lixisenatide).…”
Section: Human Versus Exendin-based Glp-1ramentioning
confidence: 99%